Plasma free polyunsaturated fatty acid levels are associated with symptom severity in acute mania - Sublette, M Elizabeth; Bosetti, Francesca; DeMar, James C; Ma, Kaizong; Bell, Jane M; Fagin-Jones, Stephanie; Russ, Mark J; Rapoport, Stanley I (Bipolar disorders, 2007)
Objectives:  Nutritionally essential polyunsaturated fatty acids (PUFAs) have been implicated as potentially important factors in mood disorders. For instance, n‐3 PUFA supplementation is reported to improve outcomes in major depressive disorder and bipolar disorder. However, the role of PUFAs in acute mania has been minimally investigated. We performed a pilot study to compare plasma levels of free (non‐esterified) and esterified PUFAs between patients in an acute manic episode and healthy volunteers, and to explore associations between symptom severity and levels of fatty acids and of the arachidonic acid metabolite, prostaglandin E2 (PGE2). Methods:  Patients (n = 10) who were medication‐free for at least two weeks and seeking inpatient admission for an acute manic episode were compared with healthy volunteers (n = 10). Symptom severity was assessed at admission and after six weeks of naturalistic treatment. Fasting baseline free and esterified plasma levels of docosahexaneoic acid (DHA, 22:6n‐3), eicosapentaenoic acid (EPA, 20:5n‐3), arachidonic acid (AA,20:4n‐6) and the AA metabolite PGE2 were determined, and PGE2 levels were tested again at six weeks. Results:  No between‐group differences were found in levels of individual or total fatty acids, or of PGE2. Among subjects, manic symptom severity correlated negatively with levels of free AA and free EPA, and positively with the free AA:EPA ratio. PGE2 levels did not differ between groups or in subjects pre‐ and post‐treatment. Conclusions:  Our preliminary results suggest that, in susceptible persons, low plasma levels of free EPA compared with AA are related to the severity of mania.